2021
DOI: 10.1007/s11845-021-02755-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of urine albumin creatinine ratio with the pediatric index of mortality 2 score for prediction of pediatric intensive care unit outcomes

Abstract: Background Predicting morbidity and mortality in a pediatric intensive care unit (PICU) is of extreme importance to make precise decisions for better outcomes. Aim We compared the urine albumin creatinine ratio (ACR) with the established PICU score, pediatric index of mortality 2 (PIM 2) for predicting PICU outcomes. Methods This cross-sectional study enrolled 67 patients admitted to PICU with systemic inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Nismath et al did a cross sectional study of 67 enrolled patients admitted to PICU for comparison of urine albumin creatinine ratio with established PICU scores. 15 They observed that median duration of hospital stay among survivors was 6 days. However the median days of stay was only 2 days among non survivors with a p value of 0.012.…”
Section: Duration Of Picu Staymentioning
confidence: 99%
“…Nismath et al did a cross sectional study of 67 enrolled patients admitted to PICU for comparison of urine albumin creatinine ratio with established PICU scores. 15 They observed that median duration of hospital stay among survivors was 6 days. However the median days of stay was only 2 days among non survivors with a p value of 0.012.…”
Section: Duration Of Picu Staymentioning
confidence: 99%